2016
DOI: 10.1111/josh.12404
|View full text |Cite
|
Sign up to set email alerts
|

Project ReFresh: Testing the Efficacy of a School‐Based Classroom and Cafeteria Intervention in Elementary School Children

Abstract: Classroom nutrition education combined with cafeteria improvement has the potential to improve diet-related behavior of elementary school children. Also, collaborative partnership between schools and extension can enhance program sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…Thereby, Hanks et al () tested an intervention making F&V more convenient and attractive and suggesting consumption norms in the form of verbal prompts. Similarly, Song, Grutzmacher, and Munger () combined in‐class nutrition education with improved food presentation, choice incentives and social interactions between canteen staff and children. By applying those changes, both studies reached an increase in the proportion of children who chose at least one serving of fruits and vegetables at lunch in the canteen.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, Hanks et al () tested an intervention making F&V more convenient and attractive and suggesting consumption norms in the form of verbal prompts. Similarly, Song, Grutzmacher, and Munger () combined in‐class nutrition education with improved food presentation, choice incentives and social interactions between canteen staff and children. By applying those changes, both studies reached an increase in the proportion of children who chose at least one serving of fruits and vegetables at lunch in the canteen.…”
Section: Resultsmentioning
confidence: 99%
“…Indiana FSDs and CHCs may benefit from utilizing (and/or continuing to utilize) the Land Grant University Extension system because Extension is already an institutionalized and active component of many communities and coalitions. For example, Extension Educators in North Dakota and Maryland spearheaded successful nutrition education interventions in schools. There are many opportunities for long‐term partnerships and consolidation of resources and skills.…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, school collaboration with the Land Grant University Extension system has promising implications for nutrition education of students and parents. 20,21 Our initial interviews with CHCs indicated that coalitions view school wellness as an opportunity to promote nutrition education, school gardens, local foods, and effective/safe utilization of foods wasted during school meals. Though FSDs and CHCs both address school wellness and nutrition, their perceived feasibility of school and community nutrition programs, as well as their priorities for accomplishing public health goals (ie, meeting federal policy requirements and/or expanding local community health promotion efforts) may vary.…”
Section: Whereasmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, House Bill 4 approved in the 2015 Texas legislative session requires public schools to provide a parent engagement plan to the state “to assist the district in achieving and maintaining high levels of parental involvement.” Recent reviews of nutrition education resources for elementary school students indicate that the most effective evidence‐based strategies for improving healthy eating in elementary school children are cross‐curricular and experiential learning approaches . Moreover, literature suggests that through such activities including staff culinary and nutrition training and engagement, school districts can enhance their school food environments and impact child dietary intake . Through CATCH, fun food experience and other school‐based activities and resources, Brighter Bites provides holistic and experiential learning opportunities for school staff, students, and families.…”
Section: Discussionmentioning
confidence: 99%